2008
DOI: 10.3855/jidc.154
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Vi Capsular Polysaccharide Synthesis in Salmonella enterica Serotype Typhi

Abstract: The synthesis of Vi polysaccharide, a major virulence determinant in Salmonella enterica serotype Typhi (S. Typhi), is under the control of two regulatory systems, ompR-envZ and rscB-rscC, which respond to changes in osmolarity. Some S. Typhi isolates exhibit over-expression of Vi polysaccharide, which masks clinical detection of LPS O-antigen. This variation in Vi polysaccharide and O-antigen display (VW variation) has been observed since the initial studies of S. Typhi. We have reported that the status of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 77 publications
1
1
0
Order By: Relevance
“…Although the location of the bands observed in the WB assay for IgG antibody isotypes was analogous, a clear diference in terms of the degree of antigenic intensity was demonstrated in the WB assay whereby PTS demonstrated a higher intensity of reaction compared to PHPS. In addition, a number of reports in the literature have delineated the presence and reactivity of Salmonella fagellin antigen with the expected molecular weight of 55 kDa [28][29][30]. In this study, the 55 kDa antigen was also detected in PTS-and PHPS-pooled serum against the IgG antibody isotype.…”
Section: Discussionsupporting
confidence: 50%
“…Although the location of the bands observed in the WB assay for IgG antibody isotypes was analogous, a clear diference in terms of the degree of antigenic intensity was demonstrated in the WB assay whereby PTS demonstrated a higher intensity of reaction compared to PHPS. In addition, a number of reports in the literature have delineated the presence and reactivity of Salmonella fagellin antigen with the expected molecular weight of 55 kDa [28][29][30]. In this study, the 55 kDa antigen was also detected in PTS-and PHPS-pooled serum against the IgG antibody isotype.…”
Section: Discussionsupporting
confidence: 50%
“…OmpR was first identified in E. coli as modulator of relative levels of major outer membrane proteins like OmpC and OmpF (Taylor et al, 1981) and, subsequently reported to be a positive regulator of the Salmonellapathogenicity island-2 (SPI-2) that modulates the S. Typhimurium intracellular lifestyle (Feng et al, 2003;Garmendia et al, 2003;Lee et al, 2000). OmpR has also been reported to control in a positive or negative manner the expression of virulence factors in other pathogens like enterohemorrhagic E. coli (Wang et al, 2021), S. Typhi (Santander et al, 2008), or Vibrio cholerae (Kunkle et al, 2020). Our findings extent this view and catalogue OmpR as a key regulator of PG metabolism and morphogenesis when S. Typhimurium colonizes the intracellular niche of eukaryotic cells.…”
Section: Introductionmentioning
confidence: 99%